Wolf Creek XVII Part 1: The future of cardiac arrest resuscitation - Robert W. Neumar (Resuscitation Plus, 2023)
The Wolf Creek Conference, initiated in 1975, is a well-established tradition providing a unique forum for robust intellectual exchange between thought leaders and scientists from academia and industry focused on advancing the science and practice of cardiac arrest resuscitation. The Wolf Creek XVII Conference was hosted by the Max Harry Weil Institute for Critical Care Research and Innovation in Ann Arbor, Michigan, USA on June 15–17, 2023. A major focus of the conference proceedings was to identify and prioritize the knowledge gaps, barriers to translation, and research priorities for six major domains in the field of resuscitation: (1) automated cardiac arrest diagnosis, (2) amplifying lay-responder response, (3) mobile AEDs, (4) physiology-guided CPR, (5) extracorporeal support, and (6) neuroprotection. In addition, industry scientists were given the opportunity to present and discuss cutting edge innovations. Finally, building off of the conference’s theme of “The Future of Cardiac Arrest Resuscitation”, the Weil Institute introduced the “Wolf Creek Innovator in Cardiac Arrest and Resuscitation Award” to recognize early career investigators who were challenging current paradigms in resuscitation science. Similar to the early Wolf Creek Conferences, the goal was to fuel active discussion and debate among leading experts to determine where future research efforts should be focused. This manuscript provides an overview of the Wolf Creek XVII conference, and the individual manuscripts within this special edition of Resuscitation Plus describe the conference proceedings and outcomes in more detail. It is our intent that these publications will provide a roadmap for important academic and commercial advances in the field of cardiac arrest resuscitation.